2019
DOI: 10.1186/s40644-019-0203-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of a machine learning method to whole brain white matter injury after radiotherapy for nasopharyngeal carcinoma

Abstract: BackgroundThe purpose/aim of this study was to 1) use magnetic resonance diffusion tensor imaging (DTI), fibre bundle/tract-based spatial statistics (TBSS) and machine learning methods to study changes in the white matter (WM) structure and whole brain WM network in different periods of the nasopharyngeal carcinoma (NPC) patients after radiotherapy (RT), 2) identify the most discriminating WM regions and WM connections as biomarkers of radiation brain injury (RBI), and 3) supplement the understanding of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…d-f model 2 using features derived from medial temporal lobe, gray matter, and white matter respectively. g-i model 3 using features derived from medial temporal lobe, gray matter, and white matter respectively matter volume decreased markedly at acute and subacute stages after radiotherapy [21][22][23]. Lin J et al observed increased cortical thickness in NPC patients in the early period after radiotherapy [24].…”
Section: Discussionmentioning
confidence: 99%
“…d-f model 2 using features derived from medial temporal lobe, gray matter, and white matter respectively. g-i model 3 using features derived from medial temporal lobe, gray matter, and white matter respectively matter volume decreased markedly at acute and subacute stages after radiotherapy [21][22][23]. Lin J et al observed increased cortical thickness in NPC patients in the early period after radiotherapy [24].…”
Section: Discussionmentioning
confidence: 99%
“…We observed some interobserver discrepancies in the interpretation of specific RQS score items: the greatest were found for RQS score items “potential clinical applicability” and “open science and data,” even if other detected disagreements claim the need for more robust and easily interpretable methodological scoring systems for radiomic studies. Globally, higher standard deviations (4, 5) were observed in the studies by Leng, Abdollahi, and Pota [ 11 , 14 , 17 ].…”
Section: Resultsmentioning
confidence: 95%
“…In addition, the lack of follow-up scans to lend support to the authors' findings is a relevant limitation. The remaining 3 papers [ 11 , 13 , 15 ] were centered on magnetic resonance imaging (MRI) data. In a similar comparison with CT-based accuracy, the application of T1-weighted pretreatment MRI [ 13 ] was able to better detect the relationship between functional and nonfunctional parotid tissue and to improve the prediction ability of late xerostomia (AUC 0.83).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies using structural MRI data have revealed that compared with patients before RT, patients with NPC have signi cantly decreased gray matter after RT, mainly involving the temporal lobe, hippocampus and the cerebellum, and that the gray matter decreases were dose-and time-dependent (Blanchard et al, 2015;Guo et al, 2018;Leng et al, 2017;Lin et al, 2017;Lv et al, 2014;Shi et al, 2018). Using diffusion tensor imaging (DTI), studies have found that RT could decrease fractional anisotropy and increase mean diffusivity of the white matter in cerebellum, temporal lobe, frontal lobe and parietal lobe in patients with NPC (Duan et al, 2016;Leng et al, 2017;Leng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%